Attenuation of hyperglycemia-induced apoptotic signaling and anti-angiogenic milieu in cultured cytotrophoblast cells. (2nd April 2016) - Cawyer, Chase; Afroze, Syeda H.; Drever, Nathan; Allen, Steven; Jones, Richard; Zawieja, David C.; Kuehl, Thomas; Uddin, M. Nasir
ABSTRACT: Objective : Preeclampsia (preE) is a hypertensive disorder that occurs 20% in diabetic pregnancy. We have shown that hyperglycemia impairs cytotrophoblast cell (CTB) function. In this study, we assess apoptotic and anti-angiogenic signaling in excess glucose-induced CTBs. Study Design : Human extravillous CTBs (Sw. 71) were treated with 100, 150, 200, 300, or 400 mg/dL glucose for 48 h. Some cells were pretreated with a p38 inhibitor (SB203580) or a peroxisome proliferator-activated receptor gamma (PPARγ) ligand (rosiglitazone) or with D-mannitol. Cell lysates were utilized to measure p38 MAPK phosphorylation, PPARγ, Bcl-2-associated-X protein (Bax), anti-apoptotic Bcl-2, caspase-9, and cyclooxygenase-2 (Cox-2) expression by western blot. Levels of the vascular endothelial growth factor (VEGF), placental growth factor (PlGF), soluble fms-like tyrosine kinase-1 (sFlt-1), soluble endoglin (sEng), and interleukin 6 (IL-6) were measured in culture media using ELISA kits. Statistical comparisons were performed using analysis of variance with Duncan's post hoc test. Results : p38 phosphorylation and PPARγ were upregulated ( p < 0.05) in CTBs treated with ≥150 mg/dL glucose compared to basal (100 mg/dL). Expressions of Bax/Bcl-2, Cox-2, and caspase-9 were upregulated ( p < 0.05) in CTBs treated with ≥150 mg/dL glucose. Secretion of sFlt-1, sEng, and IL-6 was increased while VEGF and PIGF were decreased in CTB-treated ≥150 mg/dl of glucose (* p < 0.01 for each). SB203580 or rosiglitazone pretreatment significantly attenuated hyperglycemia-induced apoptotic and anti-angiogenic signaling. D-Mannitol had no effect. Conclusion : Hyperglycemia induced apoptotic and anti-angiogenic signaling in CTBs. The observed diminution of hyperglycemia-induced signaling by SB203580 or rosiglitazone pretreatment suggests the involvement of apoptotic and anti-angiogenic signaling in CTB dysfunction.